2014
DOI: 10.1007/s10948-014-2483-6
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Superconducting Fiber

Abstract: In this study, we demonstrated superconductivity in a fiber with an yttrium barium copper oxide core and fused silica cladding. The fibers were fabricated via a modified melt-draw technique and post-process annealing treatment in excess oxygen. The fibers maintained overall diameters ranging from 100-900 microns and core diameters of 50-700 microns. Superconductivity of this fiber design was validated via the traditional four-point probe test method in a bath of liquid nitrogen at temperatures on the order of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Previous work by our group [4][5][6][7] showed that it is possible to draw superconductive YBCO, bismuth-strontium-calcium copper oxide and tin powders as well as a lead wire into glass fibres using a glass working lathe. These studies proved the possibility of manufacturing glass fibres with a superconductive core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by our group [4][5][6][7] showed that it is possible to draw superconductive YBCO, bismuth-strontium-calcium copper oxide and tin powders as well as a lead wire into glass fibres using a glass working lathe. These studies proved the possibility of manufacturing glass fibres with a superconductive core.…”
Section: Introductionmentioning
confidence: 99%
“…However, the drawn fibre lengths were restricted to a short scale due to the limited working distance of the glass working lathe as detailed in ref. [4]. Therefore, due to the lack of scalability, fibre manufacturing using the glass working lathe can only be used as a preliminary method of assessing the feasibility of the proposed drawing process.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, application in sophisticated areas such as superconductivity can be envisioned via including high transition temperature metals into fi ber. [ 72,185 ] …”
Section: Plasmonics/metamaterialsmentioning
confidence: 99%